Enhancement of tunneling currents by isoelectronic nitrogen-atom doping at semiconductor pn junctions; comparison of indirect and direct band-gap systems. (1st December 2022) - Cho, Sanghun; Nakayama, Takashi
Abstract: Enhancement of tunneling currents by the isoelectronic Al–N/N-atom doping is studied at the pn junctions made of Si, Ge, GaP, InP, and GaAs semiconductors, using the sp 3 d 5 s * tight-binding model and the non-equilibrium Green's function method. With respect to indirect band-gap systems, doping produces the impurity state in the band gap, and such a state produces resonance with conduction-band states of n-type layers under the electric field. We show that this resonance state works to decrease the tunneling length between valence-band states of p-type layers and conduction-band states of n-type layers and promotes the marked enhancement of tunneling current. As for direct band-gap systems, on the other hand, the N-atom doping not only produces the localized N-atom state in the conduction bands but also reduces the band-gap energy by lowering the conduction-band. We show that the localized N-atom state does not contribute to the tunneling current, while the band-gap reduction shortens the tunneling length a little and slightly increases the tunneling current.